The Cooperatives and their incorporation to the society of the information and the knowledge a task for the leaders (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The theme of the cooperative as a philosophy of life has been a resurgence in Venezuela, to the point that the number of registered cooperatives approaches to the three hundred thousand, which exceeds all that has happened in Latin America, such growth forces us to reflect on the future of these partnerships and the leadership they need to achieve and maintain its incorporation and retention in the information society, ie, in the postmodern and the new economy. This article walks through the present and future expectations of cooperatives, its current threats and some of the causes that have prevented its success and consolidation and that regardless of the current situation not entirely friendly, the sector maintains an importance from its social and economic. Article also discusses the leadership style or approach that these organizations must build to make the jump to postmodernity and transform the sector into a conglomerate with legitimacy and social recognition, based on its ethical business practice and contribute to national welfare. That is the subject of the article leaves "open doors" to continue on the path of research, which was based on literature review and analysis of the views expressed by different authors who are concerned about the fact and deal cooperatively.The theme of the cooperative as a philosophy of life has been a resurgence in Venezuela, to the point that the number of registered cooperatives approaches to the three hundred thousand, which exceeds all that has happened in Latin America, such growth forces us to reflect on the future of these partnerships and the leadership they need to achieve and maintain its incorporation and retention in the information society, ie, in the postmodern and the new economy. This article walks through the present and future expectations of cooperatives, its current threats and some of the causes that have prevented its success and consolidation and that regardless of the current situation not entirely friendly, the sector maintains an importance from its social and economic. Article also discusses the leadership style or approach that these organizations must build to make the jump to postmodernity and transform the sector into a conglomerate with legitimacy and social recognition, based on its ethical business practice and contribute to national welfare. That is the subject of the article leaves "open doors" to continue on the path of research, which was based on literature review and analysis of the views expressed by different authors who are concerned about the fact and deal cooperatively.
Keywords: information society; postmodernity; cooperatives; leadership; new economy